Inflation, Growth and Stabilization Policies in Italy: 1960-1984 - Paolo Onofri; Bruno Salituro (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1985)
In 1963 the Italian economy experienced, for the first time after the reconstruction period, the stringency of external constraints.
Keywords: 330